2005
DOI: 10.1097/01.olq.0000161185.06387.94
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Risk Behavior Among Hispanic Immigrant Men in a Population-Based Household Survey in Low-Income Neighborhoods of Northern California

Abstract: Recent Hispanic immigrants have less stable sexual partnerships and less health-seeking behavior, including HIV testing. Established immigrants report HIV test rates comparable to the national average.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 15 publications
4
55
0
1
Order By: Relevance
“…Despite these statistics, the majority of studies of Latino men have been conducted on men who have sex with men (MSM) [15], thus it is important to investigate prevalence rates among heterosexual Latinos as well. And while few prevalence studies have been conducted among Latino migrant men [14], the few studies that have done biological testing found low prevalence rates despite high rates of HIV/STI risk behavior [17][18][19].…”
Section: Latinos and Hivmentioning
confidence: 98%
“…Despite these statistics, the majority of studies of Latino men have been conducted on men who have sex with men (MSM) [15], thus it is important to investigate prevalence rates among heterosexual Latinos as well. And while few prevalence studies have been conducted among Latino migrant men [14], the few studies that have done biological testing found low prevalence rates despite high rates of HIV/STI risk behavior [17][18][19].…”
Section: Latinos and Hivmentioning
confidence: 98%
“…Investigations into the underlying risk factors responsible for the spread of HIV/AIDS among Latino immigrant have attributed their increased rates of infection to sexual and substance use practices. These behaviors are often mediated by level of acculturation to U.S. society (Hines & Caetano, 1998;Levy, et al, 2005). For example, as Latinas become more acculturated to American society, their substance use patterns and levels of sexual promiscuity tend to increase (Nyamathi, Bennet, Leake, Lewis, & Flaskerud, 1993).…”
Section: Hiv/aids Among Latino Immigrantsmentioning
confidence: 99%
“…Although valued by both men and women as a caring and strong characteristic, machismo also has disempowering and negative properties (Marin 2003;Sears 2008) which can significantly impact the spread of HIV. As a risk factor, machismo is often associated with the risky sexual behaviors Latino men engage in to prove their manhood and reinforce masculinity, including having multiple partners (Marin 2003;Levy et al 2005), casual sexual relationships (Pleck et al 1993), and engaging in unprotected sex (Diaz 1998;Galanti 2003;Marin 2003;Jarama et al 2005). In addition, the male pride exercised through machismo authority limits women's ability to negotiate the use of a condom and question when partners suggest the use of one.…”
Section: Machismo and Familismomentioning
confidence: 99%
“…Because of strong pressures to conform to this cultural norm, many gay/bisexual Latino men choose to hide their sexual orientation, resulting in increased risky behaviors contributing to the spread of HIV (Diaz 1997;Dolezal et al 2000;Marin 2003;Diaz et al 2004;Levy et al 2005).…”
Section: Rudymentioning
confidence: 99%
See 1 more Smart Citation